Trends for coronary heart disease and stroke mortality among migrants in England and Wales, 1979–2003: slow declines notable for some groups - Harding, S (BMJ Publishing Group, 2008)
OBJECTIVE: To examine trends in coronary heart disease and stroke mortality in migrants to England and Wales. DESIGN: Cross-sectional. OUTCOME MEASURES: Age-standardised and sex-specific death rates and rate ratios 1979–83, 1989–93 and 1999–2003. RESULTS: Coronary mortality fell among migrants, more so in the second decade than the first. Rate ratios for coronary mortality remained higher for men and women from Scotland, Northern Ireland, Republic of Ireland and South Asia, and lower for men from Jamaica, other Caribbean countries, West Africa, Italy and Spain. Rate ratios increased for men from Jamaica (1979–83: 0.45, 0.40 to 0.50; 1999–2003: 0.81, 0.73 to 0.90), Pakistan (1979–83: 1.14, 1.04 to 1.25; 1999–2003: 1.93, 1.81 to 2.06), Bangladesh (1979–83: 1.36, 1.15 to 1.60; 1999–2003: 2.11, 1.90 to 2.34), Republic of Ireland (1979–1983: 1.18, 1.15 to 1.21; 1999–2003: 1.45, 1.39 to 1.52) and Poland (1979–83: 1.17, 1.09 to 1.25; 1999–2003: 1.97, 1.57 to 2.47), and for women from Jamaica (1979–83: 0.63, 0.52 to 0.77; 1999–2003: 1.23, 1.06 to 1.42) and Pakistan (1979–83: 1.14, 0.88 to 1.47; 1999–2003: 2.45, 2.19 to 2.74), owing to smaller declines in death rates than those born in England and Wales. Rate ratios for stroke mortality remained higher for migrants. As a result of smaller declines, rate ratios increased for men from Pakistan (1979–1983: 0.99, 0.76 to 1.29; 1999–2003: 1.58, 1.35 to 1.85), Scotland (1979–1983: 1.11, 1.04 to 1.19; 1999–2003: 1.30, 1.19 to 1.42) and Republic of Ireland (1979–1983: 1.27, 1.19 to 1.36; 1999–2003: 1.67, 1.52 to 1.84). CONCLUSION: For groups with higher mortality than people born in England and Wales, mortality remained higher. Smaller declines led to increasing disparities for some groups and to excess coronary mortality for women from Jamaica. Maximising the coverage of prevention and treatment programmes is critical.